Colobomatous macrophthalmia with microcornea syndrome maps to the 2p23-p16 region - TOKER, AYŞE EBRU; ELÇİOĞLU, HURİYE NURSEL (WILEY-LISS, 2007)
Colobomatous macrophthalmia with microcornea syndrome (OMIM 602499) is a rare, autosomal dominant malformation characterized by microcornea, uveal coloboma, axial enlargement of the globe, and myopia. Using what is currently the largest described pedigree and candidate localization approach, we first excluded the candidate genes PAX2, PAX3, PAX6, and PAX9. Subsequently, the chromosome 14q24 region containing the CHX10, SIX1, and SIX4 genes were also excluded. Positive LOD scores were obtained with the DNA markers selected from the 2p23-p16 region. A maximum pail-wise LOD score of 3.61 (Theta = 0) was noted with the DNA marker D2S1788. Haplotype analysis positioned the locus between DNA markers D2S2203 and D2S1352 within a 22 Mb physical interval. This region contains major candidate genes, such as SIX2, SIX3, and CYP1B1; however, mutation analysis did not identify a Causative Mutation in these genes. Macrophthalmia, colobomatous, with microcornea (MACOM) is proposed as the gene symbol for this malformation linked to 2p23-p16. (c) 2007 Wiley-Liss, Inc.
Keywords: macrophthalmia; microcornea; coloboma; SIX2; SIX3; CYP1B1; PRIMARY CONGENITAL GLAUCOMA; CYTOCHROME P4501B1; LINKAGE ANALYSIS; OCULAR COLOBOMA; MUTATIONS; PEDIGREE; 2P21